The development and evaluation of an outcome predictive score for a neonatal intensive care unit in South Africa - Pieper, C. H. (Clarissa Hildegaard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.